Peran Pendidikan Agama Islam dalam Membangun Toleransi Antar Umat Beragama di SMKN Pembangunan Pertanian Rea Timur Polewali Mandar - Hidayat, Akmal; Idrus, Harbiah; Yulmiati, Yulmiati; Daeng Pananrang, Ayyub; Andriani, Syarifah Nadila; Yusriah, Yusriah (JITU Jurnal Ilmiah Tarbiyah Umat, 2025)
Islamic Religious Education plays a significant role in fostering tolerance in multicultural vocational school environments. This study aims to describe how Islamic Religious Education learning at SMKN PP Rea Timur contributes to building mutual respect among religious communities. The study uses a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, participatory observations, and curriculum documentation. Data were analyzed using reduction and triangulation techniques. The results show that a contextual teaching approach encourages students to understand differences, develop empathy, and practice tolerance in daily life. These findings emphasize the importance of strengthening inclusive religious values in vocational education to promote social harmony.